The Effect of Work Environment and Reward on Employee OCB with Job Satisfaction as a Mediation Variable: (Case Study on Supermarket & Wholesaler in Pamekasan) - Fajrin, Yunita Agfa; Ekowati, Vivin Maharani (Universitas Pamulang, 2024)
Human resources are an element that holds an important and indispensable role in a company, agency or organization. Companies must pay attention to good human resource management handlers so that the performance in the company runs smoothly and improves the quality and performance of its employees. This study aims to analyze the influence of the work environment on OCB, analyze rewards on OCB, analyze work environment on job satisfaction, analyze rewards on job satisfaction, analyze, indirectly analyze the influence of work environment on job satisfaction through OCB, and indirectly analyze the influence of rewards on job satisfaction through OCB. Samplingtechniques use saturated sampling techniques. The respondents used were 73 respondents. The data analysis method used is the Sructural Equation Model - Partial Leaste Square (SEM-PLS). The results of this study show that the work environment has a positive and significant effect on OCB, rewards have a positive and significant effect on OCB, work environment has a positive and significant effect on job satisfaction, rewards have a positive and significant effect on job satisfaction, work environment indirectly has a significant and positive effect on job satisfaction through OCB, and rewards indirectly has a positive and significant effect on OCB through job satisfaction.